Experimental study regarding the effects of forced ventilation on the thermal performance for super-large natural draft wet cooling towers. (5th June 2019) - Zhou, Yang; Gao, Ming; Long, Guoqing; Zhang, Zhengqing; Dang, Zhigang; He, Suoying; Sun, Fengzhong
Highlights: Thermal performance is experimentally studied for wet cooling tower with axial fan. Forced ventilation improves the inlet air uniformity under crosswind condition. Water temperature drop enhances by 6.46–13.35% at forced ventilation pattern. Merkel number enhances by 0.69–5.62% at forced ventilation pattern. Abstract: In this paper, an axial fan was introduced for thermal performance improvement of super-large natural daft wet cooling towers (S-NDWCTs), and the model experiment was performed to study the thermal performance of S-NDWCTs installed with an axial fan under windless and crosswind conditions. The experimental results manifested that, compared with traditional natural ventilation pattern, the thermal performance of forced ventilation is outstanding by analyzing the inlet air uniformity coefficient, cooling water temperature drop, Merkel number, etc. Moreover, the cooling water temperature drop is proportional to fan power under windless condition, and it enhances approximately by 12.06% at 3.77 W fan power, compared with natural ventilation pattern. Under crosswind conditions, the inlet air uniformity coefficient ( ψ ) and the water temperature difference on the water basin surface at forced ventilation pattern are more uniform than those of natural ventilation pattern, and ψ at 2.67 W condition increases by 8.08% compared with natural ventilation pattern while the crosswind velocity reaches to 0.6 m/s. Additionally, the cooling water temperature drop and Merkel number at forced ventilation pattern are also higher than those of natural ventilation pattern. Compared with natural ventilation pattern, these two parameters enhance by 6.46–13.35% and 0.69–5.62%, respectively within the experimental crosswind velocity ranges (0–0.6 m/s).